Interrelations between ToT skills, HRD skills and work performance of cocoa extension agent in Malaysia - Ibrahim, NorizatulShima (2020)
This study aims to focus on the performance of extension agents in the transfer of technology where their performance outcome would be indicated through the productivity of the cocoa bean production. Since the extension agents plays a significant role in improving farmers knowledge and skills (Iceberg Theory by Spancer & Spancer, 1993), the competency of the extension agents (EA) from west and east Malaysia was the main focus in this study. There is a dire need to improve EAs’ competencies so that they are able to assist farmers in applying new technologies and development introduced by the Malaysian Cocoa Board (MCB). The objective of the study mainly to determine the level skills of EA related to Transfer of Technology (ToT) skills and Human Resource Development (HRD) skills and Work Performance (WP) as perceived by productive cocoa grower in West and East Malaysia. The second objectives are, to determine the interrelations between HRD skills and ToT skills with WP of EA in West and East Malaysia; and thirdly is to determine which skills contribute the most to WP of EA in West and East Malaysia. This study had employed quantitative methods where a well-structured questionnaire was distributed to 668 productive cocoa farmers, where they had attended two MCB’s training programs exposed by EA and have cultivated cocoa almost 5 to 7 years old. The respondents were chosen through multi-stage sampling method (cluster and stratified random sampling). The variables of ToT were technical skills, technology delivery skills and technology evaluation skills. Whereas the variables of HRD consists of leadership skills, decision making, support skill and social skills. Based on descriptive analysis, West and East Malaysia, the level of ToT, HRD and WP respectively high. The Pearson's correlation coefficients showed a positive and strong interrelation in ToT, HRD with WP in the West Malaysia. The East Malaysia however, showed positive and moderate correlation for ToT, HRD with WP. Multiple regression analysis revealed that social skill, leadership skill, technical skill and decision making support skill from the West Malaysia have significant (p<0.05) with WP. Social skill is the factor that contributes the most to WP of EA in West Malaysia. For the East Malaysia, only three skills, i.e. decision making support skill, technical skill and leadership skill were found to be significant with WP. On the other hand, decision making support skill is the highest contributing factor to WP of EA in the East Malaysia. An overall of 63.0% (Adjusted R2=0.630) of the variation in EAs’ WP in the West Malaysia is explained by four skills. Meanwhile, for the East Malaysia, about 51.1% (Adjusted R2=0.511) of variation in work performance is explained by three skills. Findings of this study had contributed to the Iceberg theory on knowledge and skills in MCB agriculture programme planning. This study has strengthened the model by improving the extension agents’ knowledge and skills in transfer of technology and human resource development by area. The study recommends agriculture agencies need to provide suitable courses or training according to the skills required by EA to improve their WP and indirectly increase agriculture productivity. To provide a focused and appropriate course, the agency can create a mentor-mentee program. Besides, evaluate and update the performance of EA from time to time and focusing by area. This is because of every area have difference problem issues and unbalance workload with misleading focus.